Bioethanol production by fermentation of hemicellulosic hydrolysates of african palm residues using an adapted strain of scheffersomyces stipitis (2014)
Ethanol production using a strain of Scheffersomyces stipitis (Pichia stipitis) adapted to inhibitors of african palm hydrolysates was evaluated. The strain adaptation by cultivations in mediums progressively concentrated with inhibitors after 20 subcultures was achieved. Then the variables orbital agitation, medium volume and inoculum volume were studied for ethanol production, finding that orbital agitation and culture medium volume were significant on maximal ethanol concentration while culture medium volume and inoculum volume were significant on ethanol productivity. Maximal ethanol concentration and yield were 8.48 gl-1 and 0.39 gg-1 achieved with 125 rpm, 6.75x107 cells ml-11 and 140 ml of medium. Maximal ethanol productivity was 0.062 gl-1h-1 achieved with 125 rpm, inoculum of 99.63x107 cells ml-1 and 90 ml of culture medium. Yeast adaptation showed to be and good strategy to produce ethanol from hemicellulosic residues of african palm tree, avoiding the detoxification processes.